Development of an Electronic Module (E-module) Based on Quantum Learning on Living Creatures Classification Material - Mellia Laura Pitri; Zelhendri Zen; Indrati Kusumaningrum; Fetri Yeni J (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of this research is to develop a quantum learning-based e-module for class VII SMP science subjects, especially material on the classification of living things. The type of research is development research (Research and Development) with the ADDIE development model. The research development procedure consists of 5 stages: Analyze, Design, Development, Implementation, and Evaluation. Validity testing of electronic module products is carried out by 3 validators, namely 1 media validator, 1 material validator, 1 language validator. The practicality test was carried out on 1 educator and 31 students with the aim of finding out the practicality of the product being developed. The data collection tool is a questionnaire. The results of the media expert validity test were 75% in the valid category, the material expert validity test was 89.7% in the valid category, and the language validity test was 96.7% in the valid category. The results of the practicality test for educators were 79% in the practical category and the practicality test results for students were 82% in the very practical category. The effectiveness test used the t-test, the calculated t-value was 16.17. Meanwhile the t-table is 1.697, then (16.17>1.697). The calculation concluded that there was a significant difference between the pre-test and post-test. Based on the results of validity, practicality and effectiveness tests, it was concluded that the Quantum Learning-based electronic module (e-module) was suitable for use in the learning process for class VII middle school class VII material on the classification of living creatures.